Pengaruh Kualitas Pelayanan Dan Kinerja Karyawan Terhadap Kepuasan Nasabah Pada PT. BPR Artha Adyamurthi Di Kediri Tabanan - I Wayan Gede Antok Setiawan Jodi (Universitas Mahendradatta Denpasar, 2018)
Rural Banks (BPR) are one type of bank that is known to serve customers, micro, small and medium enterprises. BPR is the official banking institution regulated in the Banking Law which functions not only to channel credit in the form of working capital, investment and consumption credit but also to collect public funds in the form of time deposits, savings and other forms equivalent to it. Based on this background, the title of this research is